Spatial and Temporal Circulation of Babesia caballi and Theileria equi in France Based on Seven Years of Serological Data - Nadal, Clémence; Marsot, Maud; Le Metayer, Gaël; Boireau, Pascal; Guillot, Jacques; Bonnet, Sarah I. (Pathogens (Basel), 2022)
Caused by two blood parasites, Babesia caballi and Theileria equi, equine piroplasmosis is a tick-borne disease that poses major health and economic issues for the equine industry. Our objective was to gain insight into the spatio-temporal variations of parasite circulation in France, where the disease is known to be enzootic, but has been the subject of few studies. Seroprevalence was assessed for each parasite thanks to 16,127 equine sera obtained between 1997 and 2003 from all over France and analysed through complement fixation tests. Results indicated that 13.2% (5–27% depending on the region) of horses were seropositive for T. equi and 9.5% (3–25%) for B. caballi. Regardless of the year, horses from the southern regions of France were the most affected by B. caballi or T. equi infection, while the proportion of horses having antibodies against T. equi increased over time. These results highlight the heterogeneity of the circulation of both piroplasms, which may be linked with ecological diversity and vector distribution. Our data provide baseline information regarding the sero-epidemiology of B. caballi and T. equi infection in horses in France, making it now possible to select regions for future studies on risk factors, and design and implement effective targeted measures against equine piroplasms.